(untitled) (International Journal of Built Environment and Sustainability, 2024)
Basketball arenas are crucial spaces that must meet specific standards to ensure the sustainability of the sport and the quality of play. While Post-Occupancy Evaluation (POE) assesses these standards, it often assumes that all performance indicators are equally important, potentially leading to a gap between design intent and actual user experience. This study aims to bridge this gap by using the Analytic Hierarchy Process (AHP) to prioritize evaluation criteria for Turkish professional basketball arenas designed for national and international matches, regional/local competitions, and training programs. Existing studies and reports indicate that basketball arenas in Turkey often fall short in meeting necessary physical requirements and exhibit performance deficiencies. To address this gap, this study identifies factors determining arena performance, categorized as technical, functional, and behavioral based on Preiser’s framework. These criteria were further categorized according to different spaces within the arena, including general use areas, administrative spaces, and athlete-specific areas. A panel of expert sports facility design professionals provided judgments about the relative importance of these criteria using pairwise comparisons. The AHP method was then employed to calculate priority weights for each criterion. The results reveal the relative importance of different criteria for each space. For example, in general use areas, "furniture suitability/sufficiency" and "provision of ergonomic conditions for the disabled" ranked highest. In administrative spaces, "fire protection" and "accessibility" were deemed most important, while in athlete-specific areas, "visual and auditory privacy" and "security" took precedence. This study demonstrates the potential of AHP for developing a systematic and reliable framework for qualitative evaluations that measure user satisfaction. AHP-based evaluation models offer a valuable tool for architects, facility managers, and decision-makers to assess architectural design quality, prioritize design criteria, and support user-centered design processes.